2005
DOI: 10.1182/blood-2005-01-0316
|View full text |Cite
|
Sign up to set email alerts
|

Activation of  -diacylglycerol kinase is critical for the mitogenic properties of anaplastic lymphoma kinase

Abstract: IntroductionThe anaplastic lymphoma kinase (ALK) gene, localized on chromosome 2p23, encodes for a large, glycosylated 200-kDa membranespanning tyrosine kinase receptor whose expression is highly tissue specific, being restricted to components of the nervous system; structural homology studies place ALK within the family of insulin receptor tyrosine kinases (RTKs), with the highest homology to the leukocyte tyrosine kinase (LTK). 1,2 Involvement of ALK in the pathogenesis of hematopoietic malignancies derives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
44
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 42 publications
(76 reference statements)
3
44
0
Order By: Relevance
“…Furthermore, either pervanadate treatment of endothelial cells or constitutive activation of Lck in T cells result in tyrosine phosphorylation and activation of Dgk-a (Cutrupi et al, 2000;Cipres et al, 2003). Despite these data strongly suggest that Dgk-a is regulated by tyrosine phosphorylation, no tyrosine phosphorylation of Dgk-a had been detected upon stimulation with either HGF, VEGF, IL-2 or upon activation of the ALK receptor in different cell types (Cutrupi et al, 2000;Cipres et al, 2003;Baldanzi et al, 2004;Bacchiocchi et al, 2005).…”
Section: Introductionmentioning
confidence: 39%
See 3 more Smart Citations
“…Furthermore, either pervanadate treatment of endothelial cells or constitutive activation of Lck in T cells result in tyrosine phosphorylation and activation of Dgk-a (Cutrupi et al, 2000;Cipres et al, 2003). Despite these data strongly suggest that Dgk-a is regulated by tyrosine phosphorylation, no tyrosine phosphorylation of Dgk-a had been detected upon stimulation with either HGF, VEGF, IL-2 or upon activation of the ALK receptor in different cell types (Cutrupi et al, 2000;Cipres et al, 2003;Baldanzi et al, 2004;Bacchiocchi et al, 2005).…”
Section: Introductionmentioning
confidence: 39%
“…Activation and membrane recruitment of Dgk-a G Baldanzi et al et al, 2003;Baldanzi et al, 2004;Bacchiocchi et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously showed that DGKα is activated by growth factors on recruitment to the plasma membrane through its Src-mediated phosphorylation on Tyr 335 . Activation of DGKα mediates growth-factor-induced cell migration and proliferation in epithelial, endothelial, and lymphoma cells (8)(9)(10)(11)(12). Moreover, we demonstrated that in epithelial cells, DGKα is required for hepatocyte growth factor (HGF) -induced membrane ruffling by regulating Rac membrane targeting and activation (13).…”
mentioning
confidence: 99%